Program Literasi Digital Untuk Siswa di Sekolah Dasar - Ukhra, Rahmatul; Aifara, Tasya; Z, Zaituni; Mutia, Zulfa; Handayani, Putri; Usrina, Wirda (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Digital literacy is an urgent need in education, particularly in remote areas, to bridge the technology gap and enhance the quality of learning. This study aims to evaluate digital literacy programs for students and teachers in remote areas by highlighting the challenges and opportunities for implementation. The research employed a descriptive qualitative method, with data collection techniques including interviews, observations, questionnaires, and document analysis. The findings reveal that limited infrastructure, low teacher competency, weak managerial roles of school principals, and minimal community support are the primary challenges. Nevertheless, some schools have shown progress through community collaboration and continuous training. This study concludes that digital literacy programs require a holistic approach encompassing infrastructure development, teacher competency enhancement, policy formulation, and community involvement.